Financing to deposit ratio (FDR), pembiayaan jual beli, bagi hasil, Ijarah terhadap profitabilitas bank umum syariah - Setyaningrum, Nur Indah (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2018)
This study aims to determine the effect of FDR, buy and sell financing, profit sharing financing,ijarah financing to the profitability in general syariah bank that listing on Indonesia. This studyuses secondary data obtained from the Financial Statement Publication Data Quarter of ShariaCommercial Banks period 2012-2016 on the website of the Otoritas Jasa Keuangan. There are 3(three) syariah banks that are the sample of Bank BNI Syariah, Bank BRI Syariah and Bank BCASyariah. The data prosecced using multiple linear regression by SPSS version 23.